Implementation Of The Simple Additive Weighting And RIASEC Method In The Design Of The Best UKM Selection Application (Case Study: Dinamika University) - Parastowo, Irvan Alfaridzi Dwi; Hariadi, Bambang; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Students competing in the world of work need soft skills. Soft skills can be improved through an organizational process. Dinamika University has a Culture and Character Building (Cutting) program to help students improve their soft skills. The program is widely available for thousands of students and is organized by UKM. Even though it has many programs, there are obstacles to be faced. Based on the survey results, 25 students didn’t participate in UKM and 32 students made the wrong choice of UKM. This is because students don’t know what their talent interests are. In knowing someone's talent interest there is a model called RIASEC. Then in determining the best alternative, there is an appropriate method to use, namely Simple Additive Weighting (SAW). Based on the description, an application of the RIASEC and SAW methods is needed in the design of the best UKM field selection application. The results showed that the RIASEC and SAW methods were successfully applied to the best UKM field selection applications. A total of 97.3% of students recognized their talents from the RIASEC test results and 94.6% of students agreed that the UKMKU application was able to provide recommendations for the best selection of UKM.